2017
DOI: 10.1007/s00270-017-1768-0
|View full text |Cite|
|
Sign up to set email alerts
|

CT-Guided Percutaneous Trans-scapular Lung Biopsy in the Diagnosis of Peripheral Pulmonary Lesion Nodules of the Superior Lobes Using Large Needles

Abstract: tPLB seems to be an effective and feasible procedure, accompanied by a low risk of pneumothorax in UPLN cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
4
20
0
Order By: Relevance
“…These rates were consistent with technical success rates reported previously in studies of CT-guided trans-bone lung ablation or biopsy (91%-100%) [13][14][15], and in studies of CT-guided CL for PNs (90%-100%) [12,[16][17][18]. Previous reports regarding percutaneous needle approaches in the scapular region have reported no incidence of neurovascular injury or signi cant hemorrhage associated with such procedures [13][14][15]. In this study, no complication was observed near the scapula.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These rates were consistent with technical success rates reported previously in studies of CT-guided trans-bone lung ablation or biopsy (91%-100%) [13][14][15], and in studies of CT-guided CL for PNs (90%-100%) [12,[16][17][18]. Previous reports regarding percutaneous needle approaches in the scapular region have reported no incidence of neurovascular injury or signi cant hemorrhage associated with such procedures [13][14][15]. In this study, no complication was observed near the scapula.…”
Section: Discussionsupporting
confidence: 91%
“…An asymptomatic pneumothorax rate of 14.3% was observed in the present study, which is comparable to those observed in previous studies of CT-guided coil localization (9%-40%) [16][17][18], and studies of CTguided trans-scapular lung interventions (18%-29%) [13][14][15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study demonstrated the feasibility, safety, and clinical efficacy of preoperative CT-guided TSCL for SBPNs. During the CT-guided lung interventions, the needle pathway may be blocked by the bone structures [13,14]. In most cases, the bone structures should be avoided and an alternative pathway chosen.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the PNs can be easily detected with a needle pathway to perform the biopsy or localization, some PNs can be blocked by the scapula [13,14]. Under the typical conditions, the scapula can be punctured when performing the lung interventions for the scapulablocked lung lesions [13,14]. However, few studies have reported on trans-scapular CL (TSCL) for scapularblocked PNs (SBPNs).…”
Section: Introductionmentioning
confidence: 99%